The Importance of Student Engagement in e-Learning Environment - Jozua Ferjanus Palandi (IC-ITECHS, 2020)
The use of information technology in all areas of life has also brought its impact to the educational environment. Technology has changed the way students learn. Because engagement is an important factor in the learning process, technology facilitates students to engage in a traditional classroom. Therefore, the integration of technology in e-learning should be able to increase student engagement. Lecturers are expected to use e-learning appropriately to trigger the students’ engagement. E-learning does not only offer flexibility, but e-learning is also used to improve the interactivity between lecturers and students. This study aims to examine the factors of student engagement in an e-learning environment. On the other hand, measuring student engagement in e-learning is a difficult problem. It is necessary to discuss the factors that affect student engagement according to several frameworks. This study examined six frameworks initiated by Dixson, Meyer, Garrison, Swan, and Martin. This study also focused on the factors that mainly influence student-student, student-lecturer, and student-content interactions because these factors are related to student engagement. This study found that e-learning creates a learning environment that students need to increase their involvement.